Impact of Soy–Cow's mixed milk enzyme modified cheese on bread aroma. (15th January 2022) - Ali, Barkat; Khan, Kiran Yasmin; Majeed, Hamid; Jin, Yamei; Xu, Dan; Rao, Zhiming; Xu, Xueming
Abstract: The effect of spray-dried Soy–Cow's mixed milk enzyme modified (SC-EM) cheese on wheat dough properties and bread aroma was evaluated at either 0.1, 0.5, 1.0, 1.5 or 2.0% (w/w). Significant accumulation of amino acids and peptides of dough were noted as SC-EM cheese levels increased. After baking a total of 118 volatile compounds (VCs) were identified in breads having aldehydes, alcohols, esters and acids in major proportions. Higher contents of Maillard product 3-hydroxy-2-butanone, 2-methyl-1-propanol, phenylethyl alcohol, undecane, l -limonene, 2-pentyl furan and lipid oxidation compounds hexanoic acid ethyl ester, octanoic acid ethyl ester, decanoic acid ethyl ester, butanoic acid, hexanoic acid and octanoic acid were observed. Isoamyl alcohol, lactic acid ethyl ester, ethyl sorbate and sorbic acid were the newly identified VCs. These results revealed that SC-EM cheese could be used as improver in dough and contribution to bread aroma. Thus, SC-EM cheese has been proposed to be included in fortified bakery products. Highlights: Enzyme modified cheeses are produced at low costs and could be used as flavor ingredient to desired cheese flavor in foods. A uniquely spray-died Soy-Cow's mixed milk enzyme modified cheese (SC-EMC) in bread flavor improvement was evaluated. Higher accumulation of amino acids and peptides in dough were observed acted as flavor precursors for volatile compounds. SC-EMC fortified improved bread aroma and could be used as flavor ingredient in baking products.